Optimized Allocation of Control and Protective Devices in Electric Distribution Systems - Wesz da Silva, Luis G.; Fernandes Pereira, Rodrigo A. [UNESP]; Abbad, Juan Rivier; Sanches Mantovani, Jose R. [UNESP] (Taylor & Francis Inc, 2010)
Optimized allocation and/or reallocation of control and protective devices in distribution networks allow for better operation and improved system reliability indices. Control devices (used to reconfigure the feeders) are allocated in distribution networks to obtain an optimal operation strategy in order to facilitate power supply restoration in case of a contingency. Protective devices (used to isolate faults) are allocated in distribution systems to improve the reliability and continuity of power supply. Protective devices significantly reduce the impacts of faults in terms of customer outages and the time needed for fault location and system restoration. This work presents a mixed-integer non-linear programming model for the sectionalizing switches and protective devices allocation and/or reallocation problem. The constraints considered for the problem reflect technical and economical limitations, such as in-series protective devices coordination, number of available equipment, importance of the analyzed feeder, circuit topology, quality of power supply, and physical limitations of the system. A dedicated reactive tabu search algorithm is proposed for solving this problem. Results and optimized strategies for allocating or reallocating protection devices and switches considering a real-life network restoration are presented.
Keywords: network protection systems; restoration; reliability; reactive tabu search